“Every shoulder is different”: A qualitative study of clinicians’ insights on the causative factors and strategies of managing work-related shoulder disorders among firefighters - Temitope A. Osifeso; Joy C. MacDermid; Gojjam Limenih; Mike Szekeres; Pulak Parikh; Kenneth J. Faber (PLoS ONE, 2026)
Background Work-related shoulder disorders (WSDs) are the third most prevalent work-related musculoskeletal disorder in firefighting, a significant occupational health concern among firefighters (FFs). However, comprehensive understanding of clinician perspectives on causative factors and evidence-based management strategies remains limited. Objective To explore clinicians’ perspectives on: (a) the underlying causative factors contributing to WSDs; and (b) management strategies specific to firefighters. Methods Semi-structured interviews were conducted with 15 clinicians (11 males, 4 females) between 30–61 years of age, who had experience managing firefighters with WSDs. Data collection and analysis followed interpretive description methodology, employing iterative thematic analysis to identify recurring themes and patterns. Results Eight themes emerged: 1) The Nature of Firefighting Work Exacerbates Shoulder Injuries; 2) Work-Related Slips and Falls are Linked to Traumatic Shoulder Injuries; 3) Unequal Shoulder Injury Pattern by Sex and Work Experience; 4) Lack of Formal and Targeted Training Exercises Predisposes to Shoulder Injuries; 5) Early Diagnosis is Crucial for Effective Shoulder Management; 6) Individualized Multimodal Treatment Approaches are Key to Optimal Recovery; 7) (Re-)Education on Safe Exercise Training Minimizes Shoulder (Re-)Injuries; 8) Specialized functional Assessment and Outcome Measures could Enhance Treatment Outcomes. Conclusion Firefighter WSDs are multifactorial, exacerbated by occupational exposures, sociodemographic factors and delayed or non-specialized care. Clinicians emphasize the need for implementing targeted functional rehabilitation approaches that consider the unique physical and operational demands of firefighting duties.